The (bidirectional) associations between romantic attachment orientations and mate retention behavior in male-female romantic couples - Barbaro, Nicole; Weidmann, Rebekka; Burriss, Robert P.; Wünsche, Jenna; Bühler, Janina Larissa; Shackelford, Todd K.; Grob, Alexander (Evolution and human behavior, 2021)
Attachment orientations of anxiety and avoidance are associated with many important romantic relationship outcomes. An evolutionary perspective has informed research on the associations between attachment orientations and mate retention behaviors, which individuals perform to retain their romantic partner and maintain their relationship. In the current article, we report two dyadic studies (n = 104, United States; n = 978, Germany, Switzerland, Austria) that evaluated: (1) whether bivariate associations between attachment orientations and mate retention domains are replicable; (2) whether an individual's attachment orientation predicts their partner's mate retention behaviors; and (3) whether, over time, mate retention behaviors predict attachment orientations within couples. Results of both studies replicated previous bivariate associations between attachment anxiety and cost-inflicting mate retention behaviors. Longitudinal dyadic data from Study 2 demonstrated that cost-inflicting mate retention behaviors, specifically, predict future attachment anxiety in romantic partners. These results contribute to the emerging body of research addressing the associations between attachment orientations and mate retention behaviors, and suggest an important (bidirectional) role of attachment anxiety in predicting negative partner-directed behaviors in romantic relationships.
Gesehen am 06.12.2021